Food and nutrition education as strategy for the prevention of childhood obesity (Research, Society and Development, 2023)
Introduction: Childhood obesity is considered a public health problem, with increasing prevalence and characterized by excessive accumulation of fat in adipose tissues. Several factors may be related to the high prevalence, such as family influences, physical inactivity and cultural aspects. In view of this, Food and Nutrition Education (EAN) in the school environment, where children spend most of their day, is considered a strategy to combat this reality. Objective: To find out how food and nutrition education can contribute to reducing childhood obesity rates. Methods: The study in question is a narrative literature review, with a qualitative approach. In the search strategies, the following databases were used: Google academic, Scielo and Pubmed. Results and Discussion: In recent decades, the number of children who are exposed daily to ultra-processed foods has increased, which is one of the causes for the increase in childhood obesity. Studies show that there is a large percentage of contact with these foods from early childhood and that there are several factors that can influence eating behavior. Due to the multifactorial causes of obesity, the need for a treatment carried out by a multidisciplinary team stands out, highlighting the action of the nutritionist through EAN actions. Conclusion: It is concluded that EAN actions are extremely important in forming good eating habits and in reducing the prevalence of childhood obesity.